International conference “Problems of the history of the Caucasusˮ dedicated to the 75th anniversary of Pavel Chobanyan (1948-2017) - Monika Mirzoyan (Banber Arevelagitut'yan Instituti)
The International Conference “Problems of the History of the Caucasus” was held at the National Academy of Sciences of RA in Yerevan on March 15-16. Pavlik (Pavel) Chobanyan was born in Khanlar town of Azerbaijan SSR (native village - historical Pip-Zaglik) on March 15, 1948. In 1973, he graduated from the Department of History at Yerevan State University. From 1974-1976, he pursued Caucasian and Georgian studies at the postgraduate course of the Institute of Oriental Studies of Armenian Soviet Republic Academy of Sciences and in the Institute of Manuscripts of the Georgian Academy of Sciences under the supervision of of Georgian scholar P. Metreveli.